IMPLEMENTASI ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) SEBAGAI SISTEM PENERTIBAN PELANGGARAN LALU LINTAS DI KOTA DENPASAR - Vionita, Ni Putu Vina; Julianti, Lis (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Electronic traffic law enforcement (ETLE) is law enforcement in the traffic sector based on information technology using electronic devices in the form of cameras that can detect various types of traffic violations and provide motor vehicle data automatically based on Automatic Number Plate Recognition (ANPR). This research aims to implement and impact the implementation of Electronic Traffic Law Enforcement (ETLE) as a system for controlling traffic violations in Denpasar City. The research method that researchers use is empirical juridical research. The research results show that the implementation of ETLE has not been effective in handling traffic violations in Denpasar City. This is because there are still obstacles in implementing ETLE in terms of law enforcement factors, facilities and infrastructure factors, as well as community legal culture factors. The use of ETLE is also a form of Polri's contribution in realizing Denpasar City as a smart city and is in line with bureaucratic reform. The impact of implementing ETLE in Denpasar City is that more and more people are being recorded committing violations and have not been able to reduce of violations because the public's legal awareness is still low.